Effectiveness of Bitter melon Leaf and Fruit Extract (Momordica charantia L.) and its Combination on Antifeeding Activity and Mortality of Plutella xylostella - Farokhah, Ayun Umul; Yuliani, Yuliani (LenteraBio : Berkala Ilmiah Biologi, 2025)
Plutella xylostella is a pest that attacks plants from the Brassicaceae family. Bioinsecticides from bitter melon leaf and fruit extracts are one alternative to control P. xylostella, because they contain alkaloids, flavonoids, saponins, tannins, and the main compound is momordicin. This study aims to determine the effectiveness and interaction between the type and concentration of bitter melon leaf and fruit extracts and their combinations that have the most effect on antifeeding activity and mortality of P. xylostella. The research method used a two-factor Completely Randomized Design (CRD), namely 20%, 25%, and 30% extract concentrations, negative control (distilled water), positive control (permethrin), and types of bitter melon leaf and fruit extracts and their combinations. Data were transformed into Arcsin, then analyzed using Kolmogorov-Smirnov, homogeneity, Two Way ANOVA, and Duncan tests. The results showed the effect of extract type, extract concentration, and their interaction on anti-feeding activity and mortality of P. xylostella. The most effective treatment was the 30% combination extract because it produced a mortality value of 83.33% and inhibition of feeding activity reached 37.67%. This research can be a new alternative bioinsecticide that is environmentally friendly to control P. xylostella.